Autoethnographies on the Environment and Human Health - Zolnikov, Tara Rava (Springer International Publishing, 2018)
This book explores the link between individual lives and significant environmental issues affecting millions of people around the world. Zolnikov offers a novel perspective on the environment and human health through autoethnographic stories. Each chapter includes an overview of an environmental risk factor or issue, such as air quality, accompanied by a reflective personal story. Her experiences were gathered around the world and revolve around immersion into local cultures. Learning about environmental health through this qualitative approach will enable readers to understand how issues in the environment are currently affecting people on an individual basis.